1999
DOI: 10.3989/scimar.1999.63s1303
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and distribution of decapod crustaceans in the waters off Patagonia and Tierra del Fuego, South America

Abstract: SUMMARY: This paper comprises the decapod crustacean material collected during the "Victor Hensen" campaign 1994 and during the last phase of "Polarstern" cruise ANT XIII/4 in 1996. Sampling covered waters of medium and greater depth in the Straits of Magellan, the channels towards the south, and the area south of the Beagle Channel including the northern slope of the Drake Passage. 30 species of decapods were found, which is considered a good result taking into account that the species restricted to the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 16 publications
0
27
1
4
Order By: Relevance
“…A detailed description of the study area, location of the stations, and sampling gears employed has been published by Arntz and Gorny (1996). The material used for the present study was obtained in the area between 53º42'8'' S, 70º57'4'' W and 55º09'2'' S, 67º01'6'' W; Arntz et al (1999) provide information regarding the exact geographical locations where Austropandalus grayi were collected. Ovigerous females of A. grayi were stored immediately in a 10%-buffered formaldehyde solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the study area, location of the stations, and sampling gears employed has been published by Arntz and Gorny (1996). The material used for the present study was obtained in the area between 53º42'8'' S, 70º57'4'' W and 55º09'2'' S, 67º01'6'' W; Arntz et al (1999) provide information regarding the exact geographical locations where Austropandalus grayi were collected. Ovigerous females of A. grayi were stored immediately in a 10%-buffered formaldehyde solution.…”
Section: Methodsmentioning
confidence: 99%
“…Referring to A. grayi, virtually nothing is known about the biology and ecology of this shrimp, a shallow water species inhabiting typically the antiboreal region of South America (Holthuis, 1952;Wehrtmann and Carvacho, 1997). A recent study of the decapod fauna of the Magellan zone revealed that A. grayi was the most common caridean shrimp in the study area, occurring generally at considerably less than 100 m water depth (Arntz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few species of caridean shrimps inhabit the Southern Ocean, and all produce pelagic larvae, even those in the deep sea (Thatje et al, 2005a). Brachyuran crabs are important components of Patagonian benthic ecosystems (Arntz et al, 1999;Gorny, 1999), yet they are entirely absent from the Scotia Arc and Antarctic waters. Recent records of lithodid anomuran crabs in the Southern Ocean indicate a return of these crabs to the Antarctic, perhaps as a consequence of global warming, after their extinction in the lower Miocene ((15 Ma) (Thatje et al, 2005b).…”
Section: Crustaceansmentioning
confidence: 99%
“…E. latreillii prefers sandy sediments and is typically covered with a variety of epizoans, mainly sponges, algae and hydroids (Garth, 1957;Retamal and Yáñez, 1973). Recent studies regarding the decapod fauna in waters off Patagonia and Tierra del Fuego, South America, revealed that E. latreillii is one of the predominant shallow water species, and accounted for 19 % of the total number of decapods collected in the Straits of Magellan (Arntz et al, 1999). Thus, E. latreillii can be considered a key species of the shallow water ecosystems surrounding the southern tip of the Americas.…”
Section: Introductionmentioning
confidence: 99%